Recent advances in clinical development of leukotriene B4 pathway drugs. (October 2017) - Bhatt, L.; Roinestad, K.; Van, T.; Springman, E.B.
Highlights: Much effort has been expended toward clinical development of BLT antagonists and LTA4 Hydrolase inhibitors. To date, only one LTB4 pathway targeting drug has reached the market. At least 11 LTB4 pathway drugs have entered Phase 2 trials over the past 15 years. Three LTB4 pathway drugs remain in active clinical development. Emerging insights into biology and mechanisms support continued advancement of LTB4 pathway drugs. Abstract: The LTB4 pathway is an attractive target for therapeutic drug development. Two broad classes of drugs have been pursued: antagonists of the primary LTB4 receptors (BLT1 and BLT2) and inhibitors of LTA4 Hydrolase (LTA4H), the rate limiting enzyme in the production of LTB4. An initial wave of effort culminated in the 1990s. Over the past 15 years, a second wave of more selective drug candidates, including at least 5 BLT antagonists and 6 LTA4H inhibitors, have reached Phase 2 clinical trials. Despite the extensive efforts to discover and develop LTB4 pathway targeting drugs, only one has reached the market to date. Recently discovered complexities in the pathway and challenges in matching pathway intervention with therapeutic effect could explain the limited clinical success of LTB4 pathway drugs, even though there is a large body of scientific evidence linking LTB4 to human diseases and demonstrating efficacy of these compounds in a wide array of preclinical models. Herein, we describe the clinical programs for the most prominent recent examples from each broad class and discuss the clinical outcomes and their implications for future development of LTB4 pathway drugs.